FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI BANK DI INDONESIA PERIODE TAHUN 2008-2012 - Perwitaningtyas, Gloria Anindya; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
This study aims to examine the influence of factors Size, Type of Bank, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Listed Bank on the dependent variable is the level of banking efficiency as measured by the method of non-parametric Data Envelopment Analysis (DEA) in the period 2008-2012. The data used in this study was obtained from the Directory of Financial Statements of Bank Indonesia Banking in the period 2008-2012 were published. After passing through the stage purposive sample, then the sample is appropriate to use as much as 49 banks that includes 4 state-owned banks, 23 national private banks, 13 mixture banks and 9 foreign banks. Input variables used for the calculation of the DEA method in this study include personnel costs, interest costs, other operating costs, and profit before tax. The output variables used in this study include the placement of funds between banks, securities and loans. The results showed that the variables Size, Type Bank, CAR, and Listed Bank has a significant influence on the efficiency but variable of the LDR and the NPL does not affect the efficiency of the bank. Variable Size and Type bankÂ  has positive and significant impact on the efficiency of banks. While the CAR and Listed Bank has a negative and significant on efficiency. Of the six variables, Size variable has the greatest influence on the efficiency of banks, so the banks (management bank) are expected to pay more attention to the level of total assets to increase the efficiency of the bank.